2021
DOI: 10.1186/s40348-021-00129-5
|View full text |Cite
|
Sign up to set email alerts
|

Patho-mechanisms of the origins of bronchopulmonary dysplasia

Abstract: Bronchopulmonary dysplasia (BPD) continues to be one of the most common complications of prematurity, despite significant advancement in neonatology over the last couple of decades. The new BPD is characterized histopathologically by impaired lung alveolarization and dysregulated vascularization. With the increased survival of extremely preterm infants, the risk for the development of BPD remains high, emphasizing the continued need to understand the patho-mechanisms that play a role in the development of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 113 publications
(133 reference statements)
0
14
0
1
Order By: Relevance
“…After careful consideration, iNO can increase oxygenation, but the effect is subtle, and the longterm effect is poor, which may explain why iNO can reduce the incidence of BPD. The new BPD type mostly shown a decrease in the number of alveoli and a bigger form, high oxygen exposure and in ammation are the primary causes [21]. Early studies indicated that low levels of NO can reduce lung in ammation [22], while further investigations found that high levels of NO can also aggravate in ammation [23].…”
Section: Discussionmentioning
confidence: 99%
“…After careful consideration, iNO can increase oxygenation, but the effect is subtle, and the longterm effect is poor, which may explain why iNO can reduce the incidence of BPD. The new BPD type mostly shown a decrease in the number of alveoli and a bigger form, high oxygen exposure and in ammation are the primary causes [21]. Early studies indicated that low levels of NO can reduce lung in ammation [22], while further investigations found that high levels of NO can also aggravate in ammation [23].…”
Section: Discussionmentioning
confidence: 99%
“…ст. при уровне O2 > 60 %) и продолжительности воздействия [11,12]. Таким образом, общее впечатление от многочисленных экспериментов в течение первой половины ХIХ в. заключалось в том, что токсичность кислорода возрастала быстрее, когда фракция O2 превышала концентрацию 60 %, а также при увеличении времени его воздействия на организм.…”
Section: вестник интенсивной терапии имени аи салтанова | Annals Of C...unclassified
“…Intrauterine growth restriction (IUGR), associating with preeclampsia, twin or multiple pregnancies, and many other rare conditions influence the neonatal disease profile. Histologic CA without clinical maternal or fetal infection accelerates fetal surfactant maturity, whereas fetal infection, clinical CA, asphyxia, growth restriction, and, above all, extremely premature births may influence the risk of severe RDS and complicate the management of respiratory distress ( 8 10 ). Minimization of postnatal supplementary oxygen and mechanical ventilation requirements ( 11 ) protect the lung and other organs against inflammatory and oxidant injury.…”
Section: Introductionmentioning
confidence: 99%
“…As such, prematurity and the associated pre- and antenatal factors modify the incidence and severity of RDS ( 23 ). Inflammation and toxic oxidants may both be early precursors of premature birth and mediators that increase the risk of multiple consequences of extremely premature births ( 10 , 21 , 24 ).…”
Section: Introductionmentioning
confidence: 99%